Perawatan Space Regainer pada Premature Loss Gigi Molar Sulung Rahang Atas dan Bawah – Laporan Kasus - Anatasya Rachmadani; Jeffrey Jeffrey (Denta Journal Kedokteran Gigi, 2020)
Caries is one of the most common illnesses in children and young adults. Dental caries and dental trauma that occur in children can cause missing teeth prematurely, commonly called premature loss, which can cause occlusion abnormalities caused by narrowing of the arch. A space regainer is an active device used to recover space that has narrowed to the dental arch a result of premature loss. A 9-year-old boy accompanied by his mother came to RSGMP Unjani in 2018 with complaints of upper right and back right and lower left teeth missing because extraction. The patient's mother is worried that her replacement teeth will overlap. Intra oral examination showed tooth loss 54,75,84,85. Analysis of the model shows a narrowing of the -0.9 space in the maksila and -0.7 in the mandible. Patients were treated for maksila and mandibular removable space regainer accompanied by expansion screws. Activation of expansion screws is done once a week with ¼ turns. Space regainer treatment in this patient was done 4 times and the results were very satisfying.